2021
DOI: 10.1186/s13023-021-02104-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinics and genetic background of hereditary gingival fibromatosis

Abstract: Background Hereditary gingival fibromatosis (HGF) is a rare condition characterized by slowly progressive overgrowth of the gingiva. The severity of overgrowth may differ from mild causing phonetic and masticatory issues, to severe resulting in diastemas or malposition of teeth. Both, autosomal-dominant and autosomal-recessive forms of HGF are described. The aim of this review is a clinical overview, as well as a summary and discussion of the involvement of candidate chromosomal regions, pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…1 The main clinical manifestation is chronic and progressive gingival hyperplasia. 2,3 In severe cases, gingival hyperplasia can lead to long-term retention of deciduous or permanent teeth, irregular dentition, and mental illness, and surgical removal of excess gingiva has been the only treatment. 4 To date, researchers have located five genetic loci related to non-syndromic hereditary gingival fibromatosis named GINGF1-GINGF5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The main clinical manifestation is chronic and progressive gingival hyperplasia. 2,3 In severe cases, gingival hyperplasia can lead to long-term retention of deciduous or permanent teeth, irregular dentition, and mental illness, and surgical removal of excess gingiva has been the only treatment. 4 To date, researchers have located five genetic loci related to non-syndromic hereditary gingival fibromatosis named GINGF1-GINGF5.…”
Section: Introductionmentioning
confidence: 99%
“…4 To date, researchers have located five genetic loci related to non-syndromic hereditary gingival fibromatosis named GINGF1-GINGF5. 2,3,5 Among these loci, SOS1 gene mutation was discovered in a Brazilian family in 2002, 6 and REST gene mutation was found in a Turkish family in 2017. 7 In our previous study, we found the mutation of ZNF862 (c.2812G > A) was associated with a Chinese family.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary gingival fibromatosis is a rare condition, characterized by a slow progressive growth of the gingival mucosa, being the most common generalized form. The severity of gingival tissue growth causes phonetic and masticatory problems but can lead to diastemas or incorrect position of the teeth [12].…”
Section: Introductionmentioning
confidence: 99%
“…1 It can appear as a diffuse condition when it affects the maxilla and mandible; however, it can also exclusively affect one jaw (partly diffuse condition) or occur locally in a nodule-like form. 5 Both phenotypes occur in the primary and secondary dentitions and are commonly an autosomal dominant trait with high penetrance, but few reports have described it as an autosomal recessive inheritance. 2,6 Genetic linkage and haplotype studies in HGF patients revealed five loci in which the non-syndromic autosomal dominant form of HGF was mapped.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genetic subtypes of GF, HGF is the most frequent, with an estimated frequency of 1:175,000 and without sex predilection 1 . It can appear as a diffuse condition when it affects the maxilla and mandible; however, it can also exclusively affect one jaw (partly diffuse condition) or occur locally in a nodule‐like form 5 . Both phenotypes occur in the primary and secondary dentitions and are commonly an autosomal dominant trait with high penetrance, but few reports have described it as an autosomal recessive inheritance 2,6 .…”
Section: Introductionmentioning
confidence: 99%